A large-scale renewable electricity supply system by 2030: Solar, wind, energy efficiency, storage and inertia for the South West Interconnected System (SWIS) in Western Australia. (December 2017) - Laslett, Dean; Carter, Craig; Creagh, Chris; Jennings, Philip
Abstract: An interactive web tool was created to simulate 100% renewable electricity supply scenarios for the South-West Interconnected System (SWIS) in the south-west of Western Australia. The SWIS is isolated from other grids and currently has no available hydropower. Hence it makes a good case study of how supply and demand might be balanced on an hour-by-hour basis and grid stability maintained without the benefit of energy import/export or pumped hydroelectric storage. The tool included regional models for wind and solar power, so that hypothetical power stations were not confined to sites with existing wind farms or solar power stations, or sites with measurements of wind speed and solar radiation. A generic model for solar thermal storage and simple models for energy efficiency, distributed battery storage and power to gas storage were also developed. Due to the urgency of climate change mitigation a rapid construction schedule of completion by 2030, rather than the more common target of 2050, was set. A scenario with high wind generation, and scenarios with varying levels of solar power, wind power, distributed battery storage, energy efficiency improvements and power to gas systems were considered. The battery storage system and PV arrays were configured to provide synthetic inertia to maintain grid stability (with a small loss in capacity for each), and existing synchronous generators were kept spinning with no fuel input, adding a small increase to the electrical load demand. The level of synthetic inertia provided by battery storage was estimated for each scenario. The results indicated that a balanced mix of solar PV, solar thermal, efficiency, and storage were the most feasible to be built on a rapid time scale. The required capacity and build rate of the generation and storage systems would be reduced if energy efficiency improvements were implemented on a more rapid schedule compared to the current global improvement rate. The scenario with very high levels of wind power (∼80% generation) were found to be capable of meeting SWIS reliability criteria if very large amounts of distributed storage or some high capacity seasonal reserve generation system such as power to gas were present. High levels of battery storage capacity and efficiency improvement could be as effective as a power to gas system. It was confirmed that all scenarios provided the same or greater levels of inertia than presently provided by conventional generators. This tool showed that it is possible to examine renewable energy scenarios for regional electricity networks without high computing power. Graphical abstract: Image 1 Abstract : 100% renewable electricity simulation developed for the south west of Western Australia. Balancing supply and demand is tough: grid is isolated and no pumped hydro capacity. Solar PV, solar thermal, wind farms, battery storage, P2G and energy efficiency used. Generic solar thermal power tower two tank thermal storage model developed. Grid inertia maintained, supply and demand balanced hour by hour throughout year.